Drug delivery strategies to enhance the permeability of the blood–brain barrier for treatment of glioma - Zhang F; Xu CL; Liu CM (Dove Medical Press, 2015)
Fang Zhang, Chun-Lei Xu, Chun-Mei Liu School of Pharmacy, National First-Class Key Discipline for Traditional Chinese Medicine, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China Abstract: Gliomas are amongst the most insidious and destructive types of brain cancer and are associated with a poor prognosis, frequent recurrences, and extremely high lethality despite combination treatment of surgery, radiotherapy, and chemotherapy. The existence of the blood–brain barrier (BBB) restricts the delivery of therapeutic molecules into the brain and offers the clinical efficacy of many pharmaceuticals that have been demonstrated to be effective for other kinds of tumors. This challenge emphasizes the need to be able to deliver drugs effectively across the BBB to reach the brain parenchyma. Enhancement of the permeability of the BBB and being able to transport drugs across it has been shown to be a promising strategy to improve drug absorption and treatment efficacy. This review highlights the innovative technologies that have been introduced to enhance the permeability of the BBB and to obtain an optimal distribution and concentration of drugs in the brain to treat gliomas, such as nanotechniques, hyperthermia techniques, receptor-mediated transport, cell-penetrating peptides, and cell-mediated delivery. Keywords: glioma, blood–brain barrier, drug delivery, nanotechnology, hyperthermia, receptor-mediated transport, cell-penetrating peptides, cell-mediated delivery